2012
DOI: 10.1248/bpb.35.42
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Hura crepitans and Its Active Ingredient, Daphne Factor F3, on Dihydrotestosterone-Induced Neurotrophin-4 Activation and Hair Retardation

Abstract: Neurotrophin (NT)-4 is known to be an inducer of catagen in the hair cycle, but little is known of its role in the pathogenesis of androgenetic alopecia (AGA). We previously studied the gene expression of dermal papilla cells from AGA patients and controls and found that NT-4 was up-regulated in the AGA patients. In the present study, the etiological relationship between NT-4 and androgen, which is one of the causes of AGA, and the effect of an NT-4 inhibitor on hair growth were investigated. We established a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…Uchiyama and colleagues [45] obtained the bioactive compound in Hura crepitans stem-bark; 6,7-epoxy-5-hydroxyresiniferonol-14-(2,4-tetradecadienoate) also called daphne factor F3 (Fig. 2).…”
Section: Chemistry Of Hura Crepitansmentioning
confidence: 99%
See 3 more Smart Citations
“…Uchiyama and colleagues [45] obtained the bioactive compound in Hura crepitans stem-bark; 6,7-epoxy-5-hydroxyresiniferonol-14-(2,4-tetradecadienoate) also called daphne factor F3 (Fig. 2).…”
Section: Chemistry Of Hura Crepitansmentioning
confidence: 99%
“…They showed that Hura crepitans extract and the constituent active compound, daphne factor F3, inhibits neurotrophin-4 (NT-4) activity, thus improving hair regrowth in mice implanted with dihydrotestosterone (DHT). Their study showed unequivocally that Hura crepitans or its active compound has ameliorative effect on androgenetic alopecia (AGA) [45]. The mechanism by which Hura crepitans exerts the effect of hair growth has not been fully elucidated especially as it concerns NT-4 expression in the hair follicles of mice in which there have been implantation of DHT [45].…”
Section: Chemistry Of Hura Crepitansmentioning
confidence: 99%
See 2 more Smart Citations
“…While H. crepitans from Peru possesses hair regrowth activity, H. crepitans from Brazil is not affect hair growth. Because, the daphne factor F3 content of H. crepitans from Peru is about 30 times more than H. crepitans from Brazil [109,110]. It has been suggested that H. crepitans inhibits the retardation of hair regrowth by DHT through inhibition the neurotrophin (NT)-4 activation induced by DHT [109].…”
Section: Hura Crepitansmentioning
confidence: 99%